PENGARUH NILAI KERJA DAN KESESUAIAN NILAI KERJA INDIVIDU TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KEPUASAN KERJA - Vivi Ardianingrum; Titik Nurbiyati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
This study aimed to determine the influence of work value and work congruence on organizational citizenship behavior (OCB) and job satisfaction. The study was conducted on non medical staff, nurses and general practitioners of Yogyakarta Islamic Hospital PDHI. This study uses the population as a sample. Cluster sampling method sampling technique. The number of respondents in this study was 119 people consisting of 72 percent of men and 28 percent of women. The data analysis used multiple linear regression analysis with IBM SPSS Statistics 22 as an analytical tool. The result of the research there is significant effect of work value to job satisfaction partially. There was no significant effect on the wark congruence to job satisfaction partially. There was a significant effect on the value of work, work congruence to job satisfaction simultaneously. There was no significant effect of work value to OCB partially. There was a significant effect on the work congruence to OCB partially. There was significant influence of work value, work congruence to OCB simultaneously. There was a significant negative effect of job satisfaction on OCB partially.